Tiga Pilar Utama Peradaban Islam Dalam Lintas Sejarah (Turki Usmani, Safawiyah, Fatimiyah) - Sintia Fa’iz Rahmadina; Nova Sevila Elsanti; Ainaya Harisah; Rahma Arisanti; Umar Al-Faruq (CV. ITTC INDONESIA, 2024)
This study will discuss three major medieval Islamic empires that played an important role in the development of Islamic civilization, namely: the Ottoman Turks, the Safavid Dynasty, and the Fatimid Dynasty. These three empires reached the peak of their glory under the leadership of great figures such as Sultan Sulaiman al-Qanuni, Shah Abbas I, and Caliph al-Mu'iz Riddin Allah. All three contributed to the advancement of politics, economy, art, science, and religious tolerance. However, their decline was caused by internal factors such as weak governance, dynastic conflicts, and external pressure from foreign powers. This study reveals the dynamics of Islamic history during the period of these empires and provides important insights into their successes and failures and their relevance to the study of Islamic civilization today.